THE DAUGAVA (ZAPADNAJA DVINA) ZOOPLANKTON FROM SUROZHA (BELARUS) TO DUNAVA (LATVIA) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The research has been done on qualitative and quantitative composition of zooplankton in the Daugava between Suroza and Dunava. The investigation was carried out in July – August 2008. The collection of samples was done using the net with 65µ mesh. For analysing the abundance of zooplankton method APHA 10200 was applied. Samples from 21 places were analysed assembling from the right side, left side and midchannel of the river. Species Rotatoria, Cladocera and Copepoda were found and zooplankton communities and diversity of species in the Daugava left side, right side and midchannel were compared taking into account the factors affecting them.